Cladistics, classification and identification of the brachycercine mayflies (Insecta: Ephemeroptera: Caenidae) - Sun, Lu; Mccafferty, W. P. (Zootaxa, 2008)
The mayfly subfamily Brachycercinae (Pannota: Caenidae) is redefined and shown to be an apotypic, monophyletic group based on numerous synapomorphies, including, for example in the larvae, the presence of ocellar tubercles, an anterior row of long setae on the larval head capsule, a patch of long setae posterior to the base of the glossae, a broad prosternum, and the absence of toothlike claw denticles. Over 100 morphological characters of larvae, adults, and eggs discovered to be useful for phylogenetic analysis and diagnoses are detailed and illustrated. Thirty-eight species are recognized among the genera Brachycercus Curtis, Caenoculis Soldán, Cercobrachys Soldán, Insulibrachys Soldán, Sparbarus, n. gen., Oriobrachys, n. gen., Latineosus, n. gen., Susperatus, n. gen., and Alloretochus, n. gen., by adopting a strictly phylogenetic classification, including a first tribal classification within the subfamily. Brachycercus ojibwe, n. sp., Cercobrachys fox, n. sp., C. lilliei, n. sp., C. pomeiok, n. sp., C. winnebago, n. sp., Latineosus cayo, n. sp., L. cibola, n. sp., Oriobrachys mahakam, n. sp., Sparbarus choctaw, n. sp., S. coushatta, n. sp., S. miccosukee, n. sp., and Susperatus tonkawa, n. sp. are newly described. The Nearctic Brachycercus articus Soldán, n. syn., and B. edmundsi Soldán, n. syn., are shown to be equivalent to B. harrisella Curtis, proving the latter to be a widespread Holarctic species. Sparbarus capnicus (Zhou, Sun and McCafferty), n. comb., S. corniger (Kluge), n. comb., S. europaeus (Kluge), n. comb., S. gilliesi (Soldán and Landa), n. comb., S. japonicus (Gose), n. comb., S. kabyliensis (Soldán), n. comb., S. lacustris (Needham), n. comb., S. maculatus (Berner), n. comb., S. nasutus (Soldán), n. comb., S. tubulatus (Tshernova), n. comb., Susperatus prudens (McDunnough), n. comb., and S. tuberculatus (Soldán), n. comb., are transferred from Brachycercus. Alloretochus peruanicus (Soldán), n. comb., and Latineosus colombianus (Soldán), n. comb., are transferred from Cercobrachys. Caenis dangi (Soldán), n. comb., is transferred from Caenoculis and Brachycercinae to Caeninae, and provisionally placed in Caenis Stephens. Sparbarus flavus (Traver), n. comb., is transferred from Brachycercus and considered to be a nomen dubium. Nomenclatural history, new or revised descriptions as appropriate, diagnoses, illustrations, and keys are provided for known stage of species. Origins and evolutionary relationships of the Brachycercinae are hypothesized based on cladistic results. Brachycercinae is considered to have originated from a Caenis-like ancestor. The genera Cae-WORLD BRACHYCERCINAEnoculis and Insulibrachys represent more ancestral lineages, whereas the genera Sparbarus, n. gen., Brachycercus, Oriobrachys, n. gen., Latineosus, n. gen., Susperatus, n. gen., Alloretochus, n. gen., and Cercobrachys appear more derived. Cercobrachys pomeiok and other closely related species are most apotypic in terms of numbers of accumulated apomorphies.